Desain dan Implementasi Sistem Visible Light Communication berbasis Pulse Width Modulation - Pradana, Angga; Fuada, Syifaul; Adiono, Trio (Majalah Ilmiah Teknologi Elektro, 2018)
Design, implementation, and its evaluation of visible light communication (VLC) using 1-PWM is discussed clearly in this paper. The designed system consists of two main blocks: VLC Coordinator that cover DSP and AFE transmitter whereas the VLC client covers the DSP and AFE receiver. The Microcontroller STM32F4 board is employed as DSP device in this project, both for coordinator- and client-side.  The VLC demo shows that real-time texts streaming with 10 kb of packet size can be performed well. Our VLC system can be used optimally in 50 to 70 cm of optical channel distance with 0 degrees.  In other hands, the maximum bit-rate of this VLC system is limited to 3.3 kbps.